Synthesis and SAR Studies of Fused Oxadiazines as γ-Secretase Modulators for Treatment of Alzheimer's Disease - Huang, Xianhai (American Chemical Society, 2012)
[Image: see text] Fused oxadiazines (3) were discovered as selective and orally bioavailable γ-secretase modulators (GSMs) based on the structural framework of oxadiazoline GSMs. Although structurally related, initial modifications showed that structure–activity relationships (SARs) did not translate from the oxadiazoline to the oxadiazine series. Subsequent SAR studies on modifications at the C3 and C4 positions of the fused oxadiazine core helped to identify GSMs such as compounds 8r and 8s that were highly efficacious in vitro and in vivo in a number of animal models with highly desirable physical and pharmacological properties. Further improvements of in vitro activity and selectivity were achieved by the preparation of fused morpholine oxadiazines. The shift in specificity of APP cleavage rather than a reduction in overall γ-secretase activity and the lack of changes in substrate accumulation and Notch processing as observed in the animal studies of compound 8s confirm that the oxadiazine series of compounds are potent GSMs.